Episodic Sparse Cost Evaluation for Policy Analysis in Stochastic Shortest Path Problems: english - Fahmi Izhari; Rafi Septiawan Putra; Hasanal Fachri Satia Simbolon; Ade Linhar (Teknik Informatika Universitas Malikussaleh, 2025)
Conventional evaluations of stochastic shortest path policies typically rely on dense reward or cost signals, which often obscure rare but behaviorally critical interactions. This paper introduces an episodic sparse-cost evaluation framework that assigns costs only to a small subset of state action pairs identified through a short probing phase, thereby decoupling cost accumulation from trajectory length. The objective of this study is to assess whether episodic sparse costs can provide a more interpretable and behavior-focused evaluation of policy execution compared to dense formulations. The framework is empirically validated through controlled navigation experiments under a fixed policy in a grid-based stochastic shortest path setting. In a representative episode, the agent successfully reached the terminal state in 95 steps, while incurring only two cost-triggering events drawn from a sparse support set of size five. This resulted in a total episodic cost of 2.0 and a hit rate of 0.021, indicating that more than 97% of agent environment interactions were cost-free. The temporal distribution of costs appeared as isolated impulses rather than continuous signals, enabling precise localization of critical decision points along the trajectory. These findings demonstrate that episodic sparse-cost evaluation yields bounded, event driven cost behavior that remains stable even for long trajectories. The proposed framework offers a transparent and scalable alternative for analyzing policy behavior in stochastic environments, particularly in scenarios where rare violations, constraints, or risk sensitive interactions are of primary concern. Future research will extend this evaluation paradigm to multi-episode analysis, adaptive policies, and integration with constraint aware learning objectives.